Baayun Maulid in The Digital Public Sphere: From Multiculturalism to Interculturalism in Tolerance Education - Fauzi, Ahmad; Fuady, M. Noor (Nizham Jurnal Studi Keislaman, 2025)
The Baayun Maulid tradition, a religious and cultural expression of the Banua Halat community in South Kalimantan, embodies the harmony between Islam and local wisdom. In the age of digital globalization, this ritual transcends its local religious boundaries and becomes a site of intercultural interaction through digital public spaces such as YouTube, Instagram, and Facebook. This study aims to analyze how the digital representation of Baayun Maulid contributes to tolerance education and fosters intercultural dialogue. Using a qualitative-descriptive method with a cultural discourse analysis approach, this research reveals a paradigm shift from multiculturalism to interculturalism, which values dialogue, collaboration, and mutual exchange. The digital transformation of Baayun Maulid illustrates that Indonesian Islam, particularly in the Banjar context, can engage with global modernity while maintaining its spiritual identity. Thus, this tradition offers a locally grounded yet globally relevant model of tolerance education, enriching Islamic studies in contemporary discourse.